Research on the Cultivation of Professional Core Competencies of Secondary Vocational Accounting Students Based on the "Data-Credit-User" Model (Journal of educational development exploration, 2026)
The accounting and finance profession is undergoing a fundamental shift in the digital-intelligent era—moving from traditional bookkeeping functions toward value-creating roles. This evolution demands reconceptualization of the core professional competencies required of future accountants. Grounded in the distinctive nature of vocational education and contemporary accounting trends, this study develops a competency cultivation model for secondary vocational accounting students, structured around three core pillars: data responsibility, credit bridging, and user orientation. Empirical evidence from case studies conducted in representative Chinese vocational institutions demonstrates that the model fosters rational thinking and legal awareness through data literacy training, establishes connective pathways between individual development and sectoral progress via credit system integration, and cultivates service consciousness and value creation abilities through user-centric pedagogical practices. Together, these mechanisms generate a cascading responsibility framework encompassing accountability to oneself, the firm, end-users, and society at large. The paper further advances a tripartite implementation strategy involving curriculum redesign, pedagogical innovation, and assessment reform to operationalize the proposed model. These contributions offer both theoretical and practical foundations for educating a new generation of accounting professionals equipped for complex modern demands.
Keywords: Data literacy; Credit system; User orientation; Professional competencies; Accounting education; Vocational education